2016
DOI: 10.1007/s00256-016-2364-0
|View full text |Cite
|
Sign up to set email alerts
|

A new screening method for multidirectional shoulder instability on magnetic resonance arthrography: labro-capsular distance

Abstract: The inferior LC distance can be easily and quickly measured and used as an effective clinical screening method for atraumatic MDI of the shoulder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 17 publications
0
17
0
Order By: Relevance
“…It is not obvious, however, that in the presence of the Hill- The inferior labro capsular distance can be easily and quickly measured and used as an effective clinical screening method for multidirectional instability of the shoulder[ 1 0 7 _ T D $ D I F F ] . 16 In the recent years, a more detailed classification of the labrum lesions has been developed, and several variants of these 20 In our case, the incidence of Perthes injuries was 9%, more higher than in the publications of Waldt and Li, who present [ 1 1 9 _ T D $ D I F F ] a similar number of case. However, the Perthes lesion among all was the one that presented the lowest sensitivity (71%), as the theories supported by many authors[ 1 2 0 _ T D $ D I F F ] .…”
Section: _ T D $ D I F F ]mentioning
confidence: 44%
“…It is not obvious, however, that in the presence of the Hill- The inferior labro capsular distance can be easily and quickly measured and used as an effective clinical screening method for multidirectional instability of the shoulder[ 1 0 7 _ T D $ D I F F ] . 16 In the recent years, a more detailed classification of the labrum lesions has been developed, and several variants of these 20 In our case, the incidence of Perthes injuries was 9%, more higher than in the publications of Waldt and Li, who present [ 1 1 9 _ T D $ D I F F ] a similar number of case. However, the Perthes lesion among all was the one that presented the lowest sensitivity (71%), as the theories supported by many authors[ 1 2 0 _ T D $ D I F F ] .…”
Section: _ T D $ D I F F ]mentioning
confidence: 44%
“…The results indicated that PI capsular areas were greater in the shoulders of MDI patients than in those of controls. Lee et al (11) reported that capsular dimensions in the inferior and PI regions were significantly larger in an MDI group than in controls, and Lim et al (13) reported that inferior capsule lengths were larger in MDI patients than in controls. These findings are consistent with those of the present study.…”
Section: Discussionmentioning
confidence: 99%
“…However, the CSA values differed, and mean sagittal CSAs in the present study were smaller than those in Dewing's study, which may be due to differences in the sizes of the joint structures in the two studies. In a study by Lim et al (13), it was proposed that a threshold inferior capsule length of 16.88 mm can be used for MDI screening with a sensitivity of 76% and a specificity of 96%. However, this study was undertaken in a Korean cohort, and different results, perhaps larger values in particular, would be expected in Caucasians due to the typically larger skeletons.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations